Wildlife health outcomes and opportunities in conservation translocations. Issue 3 (26th July 2022) - Beckmann, Katie M.; Cromie, Ruth L.; Sainsbury, Anthony W.; Hilton, Geoff M.; Ewen, John G.; Soorae, Pritpal S.; Kock, Richard A.
Abstract: It is intuitive that the health status of wildlife might influence conservation translocation outcomes, however, health as a topic has received limited attention in the conservation translocation literature. We determined the forms and frequency of disease and other biological problems reported in translocated animals and plants, and in populations linked to translocation, and associations between their mention and translocation 'success'. From these problems we deduced the forms of ill‐health potentially associated with conservation translocation and developed contextual frameworks to inform health management. Using described selection criteria, a subset of case studies of animal and plant conservation translocation from the IUCN's 'Global Reintroduction Perspectives' series (2008–2018) was reviewed. Self‐reported information describing or implying mortality, ill‐health or reproductive compromise was extracted and categorized as a 'disease' or other biological problem. Problems explicitly described as a 'major difficulty', 'major lesson' or 'reason for failure' were termed 'notable'. We specified the conditions representing ill‐health and created diagrams illustrating their relationships to other biological problems and processes, and management measures. Notable 'disease' problems such as infection, (as in stress‐related) and husbandry‐related disorders were reported in 30% of 295 reviewed case studies and were more likely to be mentioned in less 'successful' projects ( P < 0.05, χ 2 test). Other biological problems, in particular predation, adverse climate or weather, and anthropogenic trauma, were commonly reported (66% of 295 studies), especially post‐release. When present, disease may be an important obstacle to translocation success. The negative health impacts of other, apparently common post‐release problems also merit acknowledgement. A broad spectrum of disease and other health‐related problems can potentially occur in conservation translocations and impact conservation and animal welfare outcomes. We suggest health management of translocation has three broad roles: to mitigate disease risks posed to other animals, plants and humans; to mitigate threats to the health of translocated individuals themselves; and to preserve and build their resilience and adaptive capacity, given the apparent high frequency of post‐release problems. We advocate a stronger emphasis on fostering health as opposed to solely preventing disease. This is directly and indirectly dependent on a range of related project management actions and on multi‐disciplinary expertise. Abstract : We explored the forms and frequency of disease and other biological problems self‐reported in animal and plant conservation translocation case‐studies, and associations between their mention and translocation 'success'. From these problems we deduced the forms of ill‐health that can be associated with conservation translocation and developed contextual frameworks to inform health management. Notable 'disease' problems such as infection, stress‐ and husbandry‐related disorders were reported in 30% (n = 89) of 295 reviewed case studies and were more likely to be mentioned in less 'successful' projects. Other biological problems, in particular predation, adverse climate or weather, and anthropogenic trauma, were commonly reported (in 66% of 295 studies), especially post‐release. When present, disease may be an important obstacle to translocation success; the negative impacts of other, apparently common post‐release problems on health also merit acknowledgement. We should aim to foster wildlife health throughout the translocation process.